Long-Term Accumulation with Latent Heat in Storage Tanks with Experimental Enhancement - Gorás Michal; Vranay František (Selected Scientific Papers: Journal of Civil Engineering)
Utilization of Thermal Tank Energy Storage Systems (TTES) for efficient storage and release of thermal energy. TTES systems are an integral part of energy infrastructures that enable the storage of surplus energy in the form of heat and its subsequent use as required. We focus on the study of the benefits and challenges associated with the implementation of TTES systems and analyze their impact on temperature stabilization, minimization of heat losses, and overall efficiency. We also discuss the flexible control of tank charging and discharging in TTES systems. Finally, we conclude by reviewing further research aimed at optimizing TTES systems to achieve sustainable and efficient use of thermal energy in the future.